Aspectos biológicos e socioculturais : uma análise das justificativas para des (legitimação) de pessoas transexuais em competições esportivas - Serrano, Jéssica Leite (2024)
In 2016, after the International Olympic Committee (IOC) changed its guidelines regarding the participation of trans athletes in the Olympics, there was a substantial growth in discussions involving this topic. Within academia, despite there being an increase in the number of studies produced on these issues, there are still many investigative gaps that are far from being addressed. In order to contribute to these discussions and give a voice to the protagonists of this topic, the main purpose of the present study was to understand the arguments used by social actors involved in sport to legitimize or delegitimize the participation of transgender people in sports competitions. The study is characterized as qualitative and exploratory research. Five trans athletes participated in the research; 4 sports coaches and 4 physiologists, who were selected through chain reference. The data collection instrument was the semi-structured interview to obtain the research analysis corpus. To analyze the data, we used discourse analysis and for this we were inspired by the works of Foucault, The order of discourse and the Archeology of Knowledge to define the discourse analysis perspective we adopted. The research was approved by the Research Ethics Committee of the Health Sciences Center (CCS) belonging to the Federal University of Paraíba (UFPB), following Resolution No. 466/13 of the National Health Council, with approval and registration at the CEP/ CCS/ UFPB and CAAE number: 29725620.0.0000.5188. The present study led to the construction of two original articles. The first aimed to analyze the experiences of trans athletes in facing the barriers found in sports spaces to be accepted as competitors. The results indicate that the main barriers faced by the athletes are the resistance of opposing teams in accepting to play against a team with a trans athlete; the need to participate in competitions based on biological sex to play volleyball; transphobia; and the lack of inclusion of organizations that are in charge of the championships. Despite the numerous barriers, the athletes demonstrated resilience, seeking to resist and persevere in the search for their rights to participate in female competitions, despite facing transphobia in different forms and proportions. The second article aimed to analyze the speeches of sports physiologists and coaches about the participation of trans people in sport. The results indicate that there is no consensus in the interviewees' speech about agreeing with the participation of trans athletes in sports competitions, the place of trans bodies in sport, in the interviewees' view, is one of separation or rejection, with the creation of a third category, the most recurring alternative regarding the place these bodies should occupy.